Technology and applications of polymers derived from biomass - Ashter, Syed Ali (Plastics Design Library, 2017)
Technology and Applications of Polymers Derived from Biomass explores the range of different possible routes from biomass to polymeric materials, including the value and limitations of using biomass in material applications and a comparison of petrochemical-derived polymers and bio-based polymers. The book discusses biomass sources, types, chemistry and handling concerns. It covers the manufacture of industrial chemicals from biomass and the derivation of monomers and polymers from biomass. It also details the processing and applications of biomass-derived polymers to enable materials scientists and engineers realize the potential of biomass as a sustainable source of polymers, including plastics and elastomers. The book is a one-stop-shop reference-giving students a basic understanding of the technology and how the material can be applied to industrial processes they will face in the workforce, and giving materials engineers and product designers the information they need to make more informed material selection decisions.